Food Intake of Overweight and Obesity in Children Aged 7-12 Years at Aceh Barat District - Sri Wahyuni Muhsin; Sukma Elida; Arif Iskandar (Journal of Nutrition Science, 2020)
Nutrition problems in Indonesia are already classified as multiple nutritional problems, namely the problem of undernutrition and overweight obesity. In 2010 the prevalence of overweight and obesity in Aceh province was 11.2 percent and in 2013 was 14.8 percent (8.9 percent fat and 5.9 percent very fat) resulting in an increase of 3.6 percent. Food intake is one factor that can cause cause overweight and obesity. This study wanted to analyze the factors of food intake in children aged 7-12 years become the cause of overweight and obesity. This study was an observational analytic study with cross sectional design aimed at assessing relationship of food intake on obesity-related weight status in first-fifth grade elementary school children aged 7-12 years at Kabupaten Aceh Barat. The sample size is 289 students. Determination of child obesity status using Body Mass Index based on Age (IMT/U), that is overweight and obesity if IMT/U>1.0 SD. Data of food intake was obtained through interview using 24-hour food recall form for 3 days. From 289 respondents, 51.90% were overweight and obesity. Factors related to the incidence of overweight and obesity are energy and fat intake (OR = 4.56 and 4.03).